2018
DOI: 10.1145/3197517.3201304
|View full text |Cite
|
Sign up to set email alerts
|

tempoGAN

Abstract: Fig. 1. Our convolutional neural network learns to generate highly detailed, and temporally coherent features based on a low-resolution field containing a single time-step of density and velocity data. We introduce a novel discriminator that ensures the synthesized details change smoothly over time.We propose a temporally coherent generative model addressing the superresolution problem for fluid flows. Our work represents a first approach to synthesize four-dimensional physics fields with neural networks. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(56 citation statements)
references
References 53 publications
0
56
0
Order By: Relevance
“…Raissi et al (2017) found that learning Navier-Stokes integration closure parameters using a neural network outperformed standard approaches. Additional advances have been made by enforcing or encouraging physical constraints and symmetries, such as the conservation of mass and energy, temporal coherence, Lyapunov stability, and Newton's laws (Erichson et al, 2019;Karpatne et al, 2017;Kim et al, 2018;Lusch et al, 2018;Reichstein et al, 2019;Stewart & Ermon, 2016;Wang et al, 2017;Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Raissi et al (2017) found that learning Navier-Stokes integration closure parameters using a neural network outperformed standard approaches. Additional advances have been made by enforcing or encouraging physical constraints and symmetries, such as the conservation of mass and energy, temporal coherence, Lyapunov stability, and Newton's laws (Erichson et al, 2019;Karpatne et al, 2017;Kim et al, 2018;Lusch et al, 2018;Reichstein et al, 2019;Stewart & Ermon, 2016;Wang et al, 2017;Xie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Looking ahead, we believe that there is a wide range of exciting future applications for our data. Beyond avenues for benchmarking, accuracy measurements, and novel reconstruction methods, we are looking forward to developments in the area of machine learning that this data will enable [Kim et al 2019;Sato et al 2018;Xie et al 2018].…”
Section: Discussionmentioning
confidence: 99%
“…To leverage machine learning in the context of simulations, researchers have, e.g., used machine learning to drive particle-based simulations [Ladický et al 2015], replaced the traditional pressure solve with pre-trained models [Tompson et al 2017], and augmented simulated data with learned descriptors [Chu and Thuerey 2017]. Others have focused on learning controllers for rigid body interactions [Ma et al 2018] or aimed for temporal coherence with adversarial training [Xie et al 2018]. This is a nascent field with growing interest, where our data set can provide a connection of simulations with the real world.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, techniques have been proposed that synthesize fluids using machine learning techniques to reduce computation time. However, since most of these techniques focus on improving efficiency, it is difficult to express high-quality liquid sheets [25][26][27][28][29].…”
Section: Related Workmentioning
confidence: 99%